hi everyone, plz don't laugh at me, i'm a math noob, i'm currently learning integrals and i got a problem. i dont understand how to solve this exercise:
∫ 4th sqrt(3x-5)³ dx (it's not 4 x, it's 4th root)
1. now...i usually take this under the brackets and derivate it:
3x - 5=t
the solution should be: I = 4 X 4th sqrt (3x-5)^7 / 21 + C
my math-english is not that good so.. this 4th sqrt should mean fourth square root
If you are learning integration you are less n00b than you think...: )
∫ [ (3x-5)^(1/4) ]^3 dx = ∫ (3x-5)^(3/4) dx
∫ (3x-5)^(3/4) dx = (3/3) ∫ (3x-5)^(3/4) dx = (1/3) ∫ 3 (3x-5)^(3/4) dx = (1/3) ∫ (3x-5)^(3/4) 3.dx =
= (1/3) ∫ z^(3/4) dz = (1/3) [ z^(3/4+1) ] / (3/4+1) +C = (1/3)(4/7) [ z^(7/4) ] + C = (4/21) (3x-5)^(7/4) + C
and that's the answer.
hey thanx for your detailed reply kylekatarn.
i dunno why i didn't think of writing that root as en exponent. i do that a lot
thanx again. i'll write back if i got some more problems
ok! I'm always here for integration problems : )
Calculus IS my favorite subject!
hey kyle...i got another one for you. i want u to solve this one, because i think that the solution in the book is not correct. the book was written by some of my teachers, they probably wrote the darn book in one night. so many mistakes.
ok here it goes:
∫ 3dx / 4(2-5x)^4/5 =
the solution given in the book goes like this:
I=-3(2-5x)^1/5 / 4 + C
The solution is correct.
I'm writting the explanation rigth now
let z = 2-5x dz = -5 dx dz = -5.dx ⌠ 3dx 3 ⌠ dx 3 1 ⌠ 5dx 3 ⌠ dz │ = -.│ = - ..│ =- .│ │ 4/5 4 │ 4/5 4 5 │ 4/5 20 │ 4/5 ⌡ 4(2-5x) ⌡(2-5x) ⌡(2-5x) ⌡z 3 let α = - and β = 4/5 to make things more clear. 20 ┌ ┐ │ -β+1 │ ⌠ dz ⌠ 1 ⌠ -β │z │ α -β+1 α│ = α│ dz = α ⌡z dz = α││ + C = .z + C │ β │ β │ -β+1 │ -β+1 ⌡ z ⌡ z └ ┘ -β+1 = 1/5 α 3 = - -β+1 4 putting everything together we get: 3 1/5 - (2-5x) + C 4
and that's it : )
Last edited by kylekatarn (2005-09-13 08:55:56)
"The physicists defer only to mathematicians, and the mathematicians defer only to God ..." - Leon M. Lederman
and once more...the day is saved by kylekatarn. THANK YOU
you're welcome :)
For future reference, if you want to ask for help, then create a new topic rather than posting on someone else's.
Anyway, for these simultaneous equations you need to scale them up so that they have a common term, then combine them to give a simple linear equation.
2x-4y=16 --> (multiply by 3) 6x-12y=48
3x+6y=-12 --> (multiply by 2) 6x+12y=-24
Add these equations together: 6x-12y+6x+12y=48-24
Knowing this, you can easily work out the other value.
It works! So your final answer is x=2, y=-3
Why did the vector cross the road?
It wanted to be normal.